PENGARUH PENGALAMAN WISATA YANG BERKESAN TERHADAP MINAT BERKUNJUNG KEMBALI DI PULAU TIDUNG, KEPULAUAN SERIBU - Susilawati, Susilawati; Sukirman, Oman; Supriyadi, Tedi (Jurnal Akademi Pariwisata Medan, 2025)
This study aims to determine the extent of the effect of memorable tourist experience on tourists’ revisit intention in Tidung Island. The research employed a quantitative approach using a correlational method and purposive sampling based on non-probability sampling, involving 100 respondents who had previously visited Tidung Island. Data were collected through a Google Form questionnaire and analyzed using IBM SPSS version 25. The results indicate that memorable tourist experience has a significant effect on revisit intention. The indicators of involvement and knowledge showed significant results in creating a memorable impression on tourists visiting Tidung Island. In contrast, the indicators of refreshment and social interactions were not sufficient to provide a significant effect on the memorable tourist experience in Tidung Island. These finding suggests that destination managers need to pay more attention to these aspects in order to enhance the value of memorable tourist experiences and motivate tourists to revisit.